Anaphylaxis as a Rare Side Effect of Pantoprazole; a Case Report - Gholamreza Faridaalaee; Javad Ahmadian Heris (Emergency, 2018)
Anaphylaxis is a serious life-threatening allergic reaction. Any medication may potentially trigger anaphylaxis, but reaction to pantoprazole is rare. Our case is a 21 year-old girl with anaphylactic reaction to pantoprazole a short time after prescription.